A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Place: England
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Publisher: Inter-Research
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Publisher: Cambridge University Press
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Hva skjedde med vågehvalen i Antarktis? - Fujise, Yoshihiro; Hatanaka, Hiroshi; Ohsumi, Seiji (Ottar, 2010)
Jakten på de store bardehvalene i antarktiske farvann startet på begynnelsen av 1900-tallet og reduserte bestandene sterkt. Vågehvalen ble mindre utsatt for fangst og fikk kanskje en fordel da de større konkurrentene forsvant? Det japanske forskningsprogrammet JARPA har studert endringer i det marine økosystemet i Antarktis.
Keywords: Sørishavet; kval; marin biologi; økosystemer

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Cruising for krill in the Southern Ocean with G.O. Sars - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Institute of Marine Research, 2010)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Genetic identification of Southern Ocean octopod samples using mtCOI - Undheim, Eivind Andreas Baste; Norman, Janette Ann; Thoen, Hanne Halkinrud; Fry, Bryan Grieg (Comptes Rendus. Biologies, 2010)
East Antarctic octopods were identified by sequencing mtCOI and using four analytical approaches: Neighbor-joining by Kimura-2-Parameter-based distances, character-based, BLAST, and Bayesian Inference of Phylogeny. Although the distance-based analytical approaches identified a high proportion of the sequences (99.5% to genus and 88.1% to species level), these results are undermined by the absence of a clear gap between intra-and interspecific variation. The character-based approach gave highly conflicting results compared to the distance-based methods and failed to identify apomorphic characters for many of the species. While a DNA independent approach is necessary for validation of the method comparisons, crude morphological observations give early support to the distance-based results and indicate extensive range expansions of several species compared to previous studies. Furthermore, the use of distance-based phylogenetic methods nevertheless group specimens into plausible species clades that are highly useful in non-taxonomical or non-systematic studies. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Publisher: Elsevier
Keywords: Sørishavet; blekksprut; genetikk; marin biologi; taksonomi

Time budgets and at-sea behaviour of lactating female Antarctic fur seals Arctocephalus gazella at Bouvetøya - Biuw, Martin; Krafft, Bjørn A.; Hofmeyr, G. J. Greg; Lydersen, Christian; Kovacs, Kit M. (Marine ecology. Progress series, 2009)
We present the first data on attendance patterns, at-sea movements and diving behaviour of Antarctic fur seals breeding at Bouvetøya (Bouvet Island), Southern Ocean. While other colonies have been extensively studied, this remote and second largest global population remains relatively unknown. Time depth recorders and satellite relay data loggers were deployed on breeding females during the 2000–2001 and 2001–2002 summers. Attendance and foraging patterns were similar to those observed at colonies in the Scotia Sea region where Antarctic krill is the predominant prey. Early to mid-lactation trips ranged within ~100 km of the island, usually towards the west. The dominant direction shifted later in the season and the range also increased markedly to a peak between early February and early March. Solar elevation influenced arrivals and departures from the island, with most departures occurring around sunset. Diurnal variations in diving behaviour were consistent with the vertical migration of krill. Diving frequency was higher at night and diving effort peaked around morning twilight. Afternoon deep diving was common, suggesting that females might target dense daytime krill aggregations between the photic zone and the thermocline. Trip durations increased throughout early to mid-lactation, peaking in late January to early March, before again decreasing towards the end of lactation. Our results illustrate the substantial variability, both between individuals and within individuals over time, that is likely to reflect variations in prey distribution and in the growth requirements of pups. Such variations need to be taken into account when estimating habitat use and resource utilisation in marine top predators.
Publisher: Inter-Research
Keywords: Bouvetøya; krill; marin biologi; pelsseler; plankton; satellittsendere; zoologi; økologi

Biologging in the Global Ocean Observing System - Boehme, Lars; Kovacs, Kit M; Lydersen, Christian; Nøst, Ole Anders; Biuw, Martin; Charrassin, Jean-Benoît; Roquet, Fabien; Guinet, Christophe; Meredith, Michael; Nichols, K; Thorpe, Sally; Costa, Daniel; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
Miniature electronic data recorders and transmitters have revolutionized the way we study animals over the past decades, particularly marine animals at sea. But, very recently, animal-borne instruments have also been designed and implemented that provide in situ hydrographic data from parts of the oceans where little or no other data are currently available (even from beneath the ice in polar regions). Ocean data is delivered from animal-borne instruments via satellites in near real-time, which would enrich the Global Ocean Observing System if animal-borne instruments were deployed systematically. In the last 10 years, studies involving more than 10 countries (Australia, Brazil, Canada, France, Germany, Greenland, Norway, South Africa, UK, USA) have demonstrated how highly accurate oceanographic sensors, integrated into standard animal, biologging instruments, can provide data of equal or better quality than XBT/XCTD data. Here, we present some of the pioneering studies and demonstrate that we now have enough information for many marine species to predict where they will go – within reasonable limits. Thus, we can direct sampling effort to particularly interesting and productive regions and maximize data return. In the future, biologging could certainly play an important part in the Global Ocean Observing System, by providing complementary data to more traditional sampling technologies - especially in the high latitudes. This paper will make a core contribution to the Plenary Sessions 4A, 4B and 5A and will be relevant to 2A, 2B and 3A.
Keywords: Bouvetøya; Sørishavet; biologging; marin biologi; oseanografi

New insights into southern ocean physical and biological processes revealed by instrumented elephant seals - Charrassin, Jean-Benoît; Roquet, Fabien; Park, Young-Hyang; Bailleul, Frédéric; Guinet, Christophe; Meredith, Michael; Nicholls, K; Thorpe, Sally; McDonald, Birgitte; Costa, Daniel; Tremblay, Yann; Goebel, Michael; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
In recent years, the international “Southern Elephant seals as Oceanographic Samplers” (SEaOS) project has deployed miniaturized conductivity-temperature-depth satellite-relayed data loggers (CTD-SRDL) on elephant seals 1) to study their winter foraging ecology in relation to oceanographic conditions, and 2) to collect hydrographic data from polar regions, which are otherwise sparsely sampled. We summarize here the main results that have been published in both science components since 2003/2004. Instrumented southern elephant seals visit different regions within the Southern Ocean (frontal zones, continental shelf, and/or ice covered areas) and forage in a variety of different water masses (e.g. Circumpolar Deep Water upwelling regions, High Salinity Shelf Water), depending on their geographic distribution. Adult females and juvenile males from Kerguelen Is. forage pelagically in frontal zones of the Southern Indian Ocean, while adult males forage benthically over the Kerguelen Plateau and the Antarctic Continental Shelf, with the two groups feeding at different trophic levels as shown by stable isotopes analysis. Oceanographic studies using the data collected from the seals have, to date, concentrated on circumpolar and regional studies of the Antarctic Circumpolar Current (ACC) circulation. The temperature and salinity profiles documented by elephant seals at high latitudes, including below sea ice, have permitted quasi-circumpolar mapping of the southernmost fronts of the ACC. By merging conventional data and the high temporal and spatial resolution data collected by seal-borne SRDLs, it has been possible to describe precisely 1) the large-scale features of the ACC in the South Atlantic and its variability; 2) the circulation pattern over the Kerguelen plateau, revealing that the poorly known Fawn Trough concentrates an important proportion of the ACC flow in that region. Seals that foraged in ice covered areas have made eulerian time series available that have allowed for the estimation of sea ice formation rates, a parameter that is otherwise difficult to obtain, while also providing a unique description of the wintertime ocean circulation over the central Weddell Sea continental shelf. Finally, we present the first data collected by a newly-developed fluorescence sensor that as been embedded in the regular CTD-SRDL and deployed on elephant seals at Kerguelen. The fluorometer data obtained have offered the first synoptic view of the 3 dimensional distribution of temperature, salinity and fluorescence over a vast sector of the Southern Indian Ocean, allowing us to describe both vertical and horizontal variations in chlorophyll. This paper will make a core contribution to the Plenary Sessions 2C, 3A and 4A, and will be relevant to 2A and 2B.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin zoologi; oseanografi

Rødt gull i Sørishavet - Stephansen, Susanne Moen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
En rekelignende skapning i Sørishavet er Kjell Inge Røkkes nye yndling. Den kan nemlig brukes i alt fra slankemidler til fiskefôr. Men vet vi nok om krill til å slippe trålerne løs? Forskningsskipet G.O. Sars har vært på tokt for å finne u mer.
Keywords: Sørishavet; krill; marin biologi

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Cetacean feeding, growth and energetics in relation to the marine ecosystem - implications for management? - Lockyer, Christina (Whaling and History II : new perspectives, 2006)
Keywords: Sørishavet; hvaler; hvalfangst; marin biologi; marine økosystemer

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene